THE GRAPHS PAYBACK WITH TECHNOLOGICAL WAYS - Ilman, V. M.; Skalozub, V. V.; Shynkarenko, V. I. (Science and Transport Progress, 2007)
It is solved the problem of graphs regenerating by their subgraphs with the help of deriving systems of graphs. In the article there is offered the algorithm of solving this problem and considered an example of graphs regenerating.